Detecting atheromatous plaques in the aortic arch or supra-aortic arteries for more accurate stroke subtype classification. (1st February 2015) - Cui, Xiaoyang; Wu, Simiao; Zeng, Quantao; Xiao, Jiahe; Liu, Ming
<x xml:space="preserve">Abstract</x> Introduction. To investigate the correlations of atheromatous plaques in the aortic arch or supra-aortic arteries with intracranial arterial stenosis and carotid plaques in stroke patients, and to determine whether taking these plaques into account will reduce the proportion of patients in the undetermined etiology group. Methods. We prospectively enrolled 308 ischemic stroke patients, whose clinical characteristics and A-S-C-O classifications were compared with analyses of intracranial arteries, carotid arteries, aortic arch, and supra-aortic arteries. Results. 125(40.6%) patients had plaques in the aortic arch or supra-aortic arteries, of which 106 (84.8%) had complex plaques. No correlations were observed between these plaques and carotid plaques ( p = 0.283) or intracranial arterial stenosis ( p = 0.097). After detecting the mobile thrombi in the aortic arch and supra-aortic arteries, the proportion of patients in the atherothrombosis group was increased from 33.8% to 55.5% ( p = 0.00), whereas the proportion of patients in stroke of undetermined etiology group was decreased from 19.2% to 11.0% ( p = 0.00). Discussion. Examining only the carotid and intracranial arteries may not provide adequate information about large arteries in stroke patients. Therefore, it would be better to include a search for relevant plaques in the aortic arch or supra-aortic arteries in modern stroke workup, for it may lead to more accurate stroke subtype classification and guide secondary prevention.